GAME EDUKASI PEMBELAJARAN BAHASA INGGRIS BERBASIS ANDROID UNTUK SDIT SABILUL QUR’AN CENDIKIA - petrus sokibi sukanto; Ady Widjaja (LPPM Institut Bisnis dan Teknologi Indonesia, 2020)
In this modern era, technology continues to evolve rapidly so that it affects us in various areas of life, especially in the field of education. Educational game is a digital game designed for educational enrichment, using interactive multimedia technology and having a good chance with game based. Android is a Linux-based operating system used for mobile phones, such as smartphones and tablet computers (PDA). In SDIT Sabilul Qur’an Cendikia, the English language learning has started from Grade 1, but in his studies, enough students are difficult to remember the English vocabulary that has been taught and sometimes students make mistakes in writing English vocabulary. This Android based educational Game is expected to be useful in the learning of Grade 1 children in SDIT Sabilul Qur'an Cendikia in learning English vocabulary and also can help teachers as alternative learning media in delivering Material about the English vocabulary.